Access and mediation transdisciplinary perspectives on attention - Wehrle, Maren; D'Angelo, Diego 1985-; Solomonova, Elizaveta (De Gruyter Saur, 2022)
Recent years have seen a rise in interdisciplinary approaches to the study of the mind. However, relatively little emphasis has been placed on attention, its functions, and phenomenology. As a result, there are a multitude of definitions and explanatory frameworks that describe what attention is, what it does, and how it works. This volume proposes that one way to discuss attention is by utilizing an integrative multidisciplinary framework that takes into consideration aspects of attention as a means of accessing the world and as a mediator of experience. It brings together contributions from cognitive science, philosophy, and psychology in order to shed light on these aspects of attention. By including both theoretical and empirical approaches to attention, this volume will provide (1) an innovative framework for examining attention as something that mediates experience and (2) new perspectives on foundational and defi nitional issues of what attention is and how it contributes to our ability to access the world. By drawing together different disciplines, this volume broadens the concept of attention. It opens up a new way of looking at attention as an active process through which the world is disclosed for us
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Mrz 2022)
Keywords: Aufmerksamkeit; Kognition; Mediation; Philosophie; Zugang; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General